Long-Term Dynamics and Medium-Term Prognosis for Glaucoma Incidence in the Amur Region - A. S. Vydrov; E. N. Komarovskikh; V. E. Piskun (Российский офтальмологический журнал)
The epidemiological situation of glaucoma has been noted to deteriorate throughout Russia and the Amur region in particular. The overall incidence of glaucoma for 1990-2014 (as estimated by referral), increased by 102.6 %: from 3.9 to 7.9 ‰. The primary incidence of glaucoma (by referral) for the same period increased by 75 % - from 0.4 to 0.7 ‰. The overall incidence of glaucoma (by referral) among urban population increased by 162.5 % - from 4.0 to 10.5 ‰. Among rural population, the overall incidence of glaucoma (by referral) increased by 94.4 %, from 1.8 to 3.5 ‰. The primary incidence among urban population of the Amur Region during the period under review increased by 400 % from 0.3 to 1.5 ‰. Among rural population, the primary incidence (by referral) increased by 100%, from 0.3 to 0.6 ‰. Our medium-term forecasts show that by 2019 we can expect further increase of general and primary morbidity of glaucoma in the Amur region, more pronounced among urban population. An increase in glaucoma incidence is probably due, first of all, to an increase in life expectancy and in the rising share of people of elderly and advanced age in the population of the region. However, it should not be disregarded that considerable deterioration in the early diagnosis of glaucoma is associated with the lack of compulsory tonometric examination for patients aged 40 or more who referred to a medical facility for the first time this year // Russian Ophthalmological Journal, 2016; 2: 23-6 . doi: 10.21516/2072-0076-2016-9-2-23-26 .